Radicalism Among Indonesia’s Young Generation: How to Overcome It? - Maunah, Alfi (Indonesian Journal of Counter Terrorism and National Security, 2022)
Indonesia is a multicultural country that has diverse ethnicities, religions, and cultures so that it has a great opportunity for various understandings to enter the Indonesian state. One of them is radicalism or often referred to as radicalism. With this opportunity, radicalism will easily enter the Indonesian state if citizens do not have a strong understanding of something, especially about the morals of the Indonesian nation itself. In this case, radicalism often spreads among the younger generation. So many things need to be considered from the impact of radicalism in the future. The psychological condition of the young generation is very easy for new ideas to enter. The younger generation, especially teenagers, are the targets of radical groups because adolescence is a period that is vulnerable to being influenced by the free environment. At the time of adolescence, the younger generation will look for identity and desire to set a vision and mission for the future. Counseling guidance services. Therefore, this scientific work intends to discuss further about the dangers of radicalism.